Initial validation of the LSPain scale: a behaviour-based clinical tool for canine lumbosacral pain - Medina-Serra, Roger; Sanchis-Mora, Sandra; Ruiz, Clara Conde; Aprea, Francesco; Belda, Eliseo; Laredo, Francisco G.; Cabezas, Miguel Ángel (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to validate the LSPain Scale, a novel 4-point ordinal instrument for assessing lumbosacral pain in dogs based on behavioural responses to palpation of the lumbosacral region.MethodsA preliminary analysis was conducted using clinical data to inform sample size estimation and to explore the scale’s convergent validity and responsiveness. Subsequently, a prospective validation was performed using 50 anonymised clinical videos retrospectively collected from client-owned dogs evaluated for suspected lumbosacral pain. Dogs represented a broad clinical spectrum and were graded using the LSPain Scale, where scores range from 0 (no pain) to 3 (severe pain). Trained observers, including pain specialists and general practitioners, independently scored the videos while blinded to clinical data.ResultsPsychometric evaluation demonstrated strong convergent and discriminant validity, responsiveness to treatment, inter- and intra-rater reliability, and usability across experience levels.DiscussionThe findings support the LSPain Scale as a valid and reliable clinician-based tool for standardised assessment and monitoring of lumbosacral pain in dogs.